KARAKTER BERBICARA DOSEN PADA MATA KULIAH SOSIOLINGUISTIK - Sabila, Amy (JURNAL PESONA, 2015)
Abstract This study aimed to obtain a description of the characteristics of talk learning a language lecturer in sociolinguistics (bilingualism and diglossia). The method used in this study is a qualitative method of data collection and data analysis. At the stage of data collection and analysis of data used refer to the method and note. The technique used in this study are freely refer to the technique involved capably (SBLC), competent engineering and technical notes. The data source of this research is a lecturer who conduct learning activities by taking into account the characteristics of speech and use of language. Research result showed that there were 103 utterances of the four types of activities of lecturers, which explains, asks, ruled, and strengthen. Activities to explain as much as 89 utterances, then followed by asking 12 speech activity, as well as govern the activities and there are 2 amplifies speech. Of all the characteristics that dominate talk is characteristics explained by using interrogative sentence as much as 89 utterances. Case is because the lecturers use the lecture method because the material is considered support to speak a lot in class.Keywords: Characteristics of Speech, Language Lecturer, Sosiolinguistic, Bilingualism and Diglossia.